2010
DOI: 10.1097/icu.0b013e32833b7aab
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival melanoma: pitfalls and dilemmas in management

Abstract: The management of conjunctival surface melanomas is complicated by local recurrence and metastatic disease, particularly for lesions greater than 2 mm in thickness and arising from nonbulbar conjunctiva. Early complete excision with appropriate adjuvant cryotherapy and topical chemotherapy may be curative in some patients. Conjunctival anatomy and high recurrence rate with resultant metastatic spread undermines the utility of sentinel lymph node biopsy in this condition. Further research and innovation for det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 59 publications
2
45
1
8
Order By: Relevance
“…It occurs more commonly in Caucasian populations and in middleaged and elderly individuals (13). The rate of local recurrence is high, between 26%-61% at 5 years and 38%-69% at 10 years (15)(16)(17)(18)(19) after diagnosis. Disease-related mortality at 10 years ranges from 13% to 38% (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…It occurs more commonly in Caucasian populations and in middleaged and elderly individuals (13). The rate of local recurrence is high, between 26%-61% at 5 years and 38%-69% at 10 years (15)(16)(17)(18)(19) after diagnosis. Disease-related mortality at 10 years ranges from 13% to 38% (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Furthermore, the mortality rate is high, ranging from 13% to 38% after 10 years. [9][10][11] In this malignancy, essential mutations occur in the B-RAF and N-RAS genes.…”
mentioning
confidence: 99%
“…These findings raise the case against the indiscriminate use of orbital exenteration, which could be reserved for T4 and selected T3 cases, since no real improvement in survival is obtained with this procedure. However, recently, other studies have found greater significance for multi-focality and status of surgical margins, which may require surgery that is more extensive and/or radiotherapy to achieve local control (16) . Therefore, our results show that the use of chemotherapy alone or combined with radiotherapy appears to give a survival benefit to our patients (not extensively analyzed because of the small number of patients of our series) and it helps to plan the surgical treatment with a less invasive approach.…”
Section: Discussionmentioning
confidence: 99%